2001
DOI: 10.1080/09540120120043955
|View full text |Cite
|
Sign up to set email alerts
|

'Don't know' and 'didn't think of it': Condom use at first intercourse by Latino adolescents

Abstract: We examined the specific reasons Latino adolescents did or did not use condoms at first intercourse and their specific reasons for their perceived risk for contracting HIV. Latino adolescents (n = 618), ages 11-19, completed a face-to-face interview that included information on demographics (sex, age, family-status (lives with both natural parents versus other family structure) and country of birth) and sexual behaviour. The respondents cited 'don't know' (25.9%), 'not available' (25.9%) and 'didn't think of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The prevalence of condom use in this study is consistent with that in China (29.6%) (10) and Thailand (28.3%) (18) but is much lower than that among European (12) and American adolescents (46%-62%) (11,19). Similar to other East Asia countries, the low prevalence of safe sex behavior among adolescents and youths in their premarital period may stem from the pervasive social stigma against premarital sex.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of condom use in this study is consistent with that in China (29.6%) (10) and Thailand (28.3%) (18) but is much lower than that among European (12) and American adolescents (46%-62%) (11,19). Similar to other East Asia countries, the low prevalence of safe sex behavior among adolescents and youths in their premarital period may stem from the pervasive social stigma against premarital sex.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with studies in the United States [26], [38], Latin America [39], sub-Saharan Africa [10], [28], and Europe [40] showing that early use is associated with subsequent use. To the best of our knowledge, the current study is the first to isolate the important positive association of condom use at sexual debut even with high-risk sexual behaviours (such as sex with non-regular partners), and to demonstrate that this relationship is consistent across multiple time points and over multiple geographical locations.…”
Section: Discussionsupporting
confidence: 91%
“…Other personal and sociodemographic factors have been shown to influence adolescents’ sexual behavior, including condom use and intentions, and were therefore included as covariates in this study. Given that prior studies with adolescents have found that sexual beliefs and behaviors are related to age (Manlove, Ikramullah, & Terry-Humen, 2008), gender (Nahom et al, 2001; Sneed et al, 2001; Tschann, Flores, De Groat, Deardorff, & Wibbelsman, 2010), parent education (Longmore, Manning, Giordano, & Rudolph, 2003), acculturation (Afable-Munsuz & Brindis, 2006; Deardorff et al, 2013; Pasch et al, 2006), and sexual experience (Nahom et al, 2001), these were included as covariates in our study.…”
Section: Present Studymentioning
confidence: 99%